Eliciting indigenous knowledge to predict climate events for the food security of agro-pastoral households in North Benin - Egah, Janvier; Yegbemey, Rosaine N.; Idrissou, Fadilath Abikè; Baco, Mohamed Nasser (Frontiers in Environmental Economics, 2023)
Populations are subjected to climatic uncertainties, the predictions of which are major challenges for the scientific community. This study analyzes indigenous climate event prediction and adaptation based on indigenous knowledge in North Benin. A sample of 80 holders of indigenous knowledge of prediction of climate events was selected using snowball sampling in the district of Gogonou. Data were collected during semi-structured interviews with the indigenous knowledge holders. Data included the profile of the knowledge holders, climate events and their prediction signs, and the planned responses in the face of climate events. Data were analyzed using discourse analysis and descriptive statistics. The results showed that the holders of indigenous knowledge of prediction of climate events are agropastoralists and some of their wives. They are over 60 years old and rooted in traditional religion. Climate events predicted were floods, pockets of drought, early cessation of rains, and invasion of fields by caterpillars. These climate events are predicted from animal, vegetable, and nature behaviors. The responses developed in the face of climate events are mainly the relocation of fields to firm land, the use of drought-tolerant varieties, the relocation of planting periods, and the planning of the suspension of children's schooling for spreading and planting operations. These findings demonstrate the necessity for policymakers to consider the value of indigenous knowledge to reduce the effects of climate change.